2009
DOI: 10.1111/j.1365-2605.2008.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐fertilization effects of chronic renal failure in male rats

Abstract: We evaluated the potential for growth and intrauterine development of embryos generated from the fertilization of oocytes with spermatozoa recovered from animals with chronic renal failure (CRF). Group A included sham-operated rats (n = 28), group B1 involved CRF rats that had undergone erythropoietin plus bromocryptine treatment (n = 28), and group B2 included CRF rats that had received normal saline. Embryos derived from the in vitro fertilization of oocytes with spermatozoa recovered from rats of group A or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(138 reference statements)
0
4
0
Order By: Relevance
“…The mission of the male gamete is not only to fertilize the oocyte but also to transfer its information to the oocyte. This is essential to early embryonic development and embryonic capacity for implantation [Dimitriadis et al 2009a;Dimitriadis et al 2009b;Tsounapi et al 2016]. It would be of clinical significance to compare the live birth rates additionally to the pregnancy rates among the three surgical approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The mission of the male gamete is not only to fertilize the oocyte but also to transfer its information to the oocyte. This is essential to early embryonic development and embryonic capacity for implantation [Dimitriadis et al 2009a;Dimitriadis et al 2009b;Tsounapi et al 2016]. It would be of clinical significance to compare the live birth rates additionally to the pregnancy rates among the three surgical approaches.…”
Section: Discussionmentioning
confidence: 99%
“…For each quantitative variable Bartlett's test of homogeneity of variance was used to determine if the groups had equivalent variances; if the variances were equivalent, the groups were compared by one-way ANOVA , and if there were significant differences by ANOVA , then Duncan's multiple comparison test was used. If the groups did not have equivalent variance in one variable, the Kruskal-Wallis one-way ANOVA was used to assess the overall effects, as previously described [14]. In this case, whenever differences were significant, pair-wise comparisons were made using the Mann-Whitney U -test.…”
Section: Methodsmentioning
confidence: 99%
“…A study by Yu et al showed that renal transplantation could improve spermatogenesis in uremic patients (22). The results of another study on rats with chronic renal failure who received bromocryptine plus to erythropoietin showed that these drugs could protect sperm DNA from oxidative damage and improve reproductive function (23).…”
Section: Discussionmentioning
confidence: 99%